Καπετάν Ναούμης, Καπετάν Ζέρβας, Καπετάν Πόνης, Καπετάν Φαρμάκης, Νικόλαος Αργυριάδης
Περιλαμβάνει αποκόμ,ματα και πορσωπικές σημειώσεις σχετικά με τους : α) Καπετάν Ναούμη, β)Καπετάν Ζέρβα, Καπετάν Πόνη, Καπετάν Φαρμάκη, Νικόλαο Αργυριάδη